Psychological wellbeing and use of alcohol and recreational drugs: results of the British HIV Association (BHIVA) national audit 2017. Issue 6 (22nd April 2019) - Parry, S; Curtis, H; Chadwick, D; ,
Abstract : Objectives: The aim of this national audit was to assess adherence of services providing HIV care in the UK to national standards and guidelines regarding psychological support and the assessment of alcohol and recreational drug use (including chemsex drugs) in people living with HIV (PLWH). Methods: Participating sites completed a survey of their services' care pathways relating to psychological support and substance use. They performed a case‐note review of up to 40 adult PLWH per service, reviewing sociodemographic and clinical information and assessment of psychological wellbeing, drug use and alcohol use. The surveys and case notes were assessed against relevant British HIV Association (BHIVA) guidelines and standards. Results: The survey was completed by 112 services. Of these, 73%, 82% and 73% had formal annual processes for assessing the psychological wellbeing, alcohol use and drug use, respectively, of PLWH. Case‐note data were provided for 4486 PLWH from 119 sites. Audited rates of assessment of PLWH were 66.0% for psychological wellbeing, 68.0% for alcohol use, 58.4% for recreational drug use and 16.8% for chemsex drug use. Variation between clinical services was wide, with ranges from < 10% to 100% routinely assessing PLWH for each of these domains. Services using assessment tools performed better. Conclusions: Assessment of PLWH for psychological wellbeing and alcohol and recreational drug use is variable in UK clinics, with a significant minority of services not documenting that they assessed these factors routinely. Wider adoption of assessment tools or proformas to assess PLWH in these areas is likely to improve surveillance for psychological morbidity and problematic alcohol or drug use.